PELATIHAN DAN PENDAMPINGAN PENULISAN KARYA ILMIAH PADA MAHASISWA TINGKAT AKHIR KAMPUS B UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA - Fekri, Latifa; Adimu, Hasan Eldin; Hasidu, La Ode Abdul Fajar; Saleh, Ramlah; Tasabaramo, Ilham Antariksa (Jurnal Abdi Insani, 2024)
The aim of holding this training activity is to train prospective graduates and prepare final year students in writing scientific papers according to writing rules. Training activities and assistance in writing scientific papers were carried out at campus B, Sembilanbelas November Kolaka University, involving final year students of the Marine Science and Fisheries Science Study program, Faculty of Agriculture, Fisheries and Animal Husbandry. Before and after implementation, students are given a questionnaire sheet as an activity evaluation sheet. During implementation, students were able to participate very enthusiastically in all stages of the training, starting from explanations and discussions regarding scientific writing theory to the practice of writing scientific papers (in the form of scientific papers). Training activities and written assistance improve students' knowledge and skills in writing scientific papers.